2022
DOI: 10.3892/ijo.2022.5379
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to escalating olaparib does not induce acquired resistance to PARPi and to other chemotherapeutic compounds in ovarian cancer cell lines

Abstract: Poly (ADP-ribose) polymerase (PARP)-inhibitors (PARPi) such as olaparib and niraparib are currently used as a treatment option for BRCA -deficient tumors and also show efficacy in platinum-sensitive tumors. However, resistance to PARPi occurs in numerous patients and in particular acquired PARPi resistance presents a major obstacle in the treatment of these tumors. In the present study, it was investigated whether stepwise exposure of ovarian cancer cells to escalating concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…Our model is principally in line with previous studies in experimental models of ovarian cancer, reporting on the emergence of an acquired phenotype of PARPi resistance after long-term PARPi exposure [17,[19][20][21]. Still, one previous study reported that olaparib exposure is unlikely to produce an acquired resistance phenotype [22]. This could be due to a completely different schedule of olaparib exposure in this study, with several cycles of 48 h treatment followed by drug-free recovery after each cycle.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our model is principally in line with previous studies in experimental models of ovarian cancer, reporting on the emergence of an acquired phenotype of PARPi resistance after long-term PARPi exposure [17,[19][20][21]. Still, one previous study reported that olaparib exposure is unlikely to produce an acquired resistance phenotype [22]. This could be due to a completely different schedule of olaparib exposure in this study, with several cycles of 48 h treatment followed by drug-free recovery after each cycle.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, critical assessment is highly important when comparing and interpreting results of these models. While in the majority of reports, PARPi-resistant cells have successfully been established by long-term PARPi exposure, one study reported that olaparib exposure is unlikely to produce an acquired resistance phenotype [22], indicating that in vitro models of PARPi resistance are neither interchangeable nor generalizable.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of drugs at passage 1 was performed with different PARPi (olaparib, niraparib and talazoparib) and carboplatin using a concentration causing approximately 10% growth inhibition (IC 10 ) [ 36 ] for additional five passages. Dropout values represent the fold-change of the percentage of EGFP + or mOrange + cells at each passage, relative to passage 0 (3 days after transduction) and was used as a readout of effects on cell fitness or drug sensitivity conferred by the CRISPR- Cas9 mediated gene mutations.…”
Section: Methodsmentioning
confidence: 99%